Modeling Of Stunting Prevelence Reduction In Toddlers By Securing Household Waste (Based On The Health Belief Model Theory) - Fadilah, Mariatul; Andrean, Andy; Trinita, Melros (Advances in Social Sciences Research Journal, 2020)
Stunting is a condition of nutritional deficiencies caused by insufficient long-term nutritional intake. It is estimated that one in four children under the age of five fails to grow along the optimal trajectory set in the World Health Organization's Child Growth Standards. This study aims to find a model of reducing the prevalence of stunting in children under five in the city of Palembang through processing household waste. This research was an analytic observational study through a quantitative approach and cross-sectional study design. In this study, the population is all mothers who have children under five (0-59 months) who check the condition of their children in the working area of ​​Palembang city health center. Each increase in 1 unit of perception of seriousness increases 0.074 units of Securing Household Waste Behavior (p value = 0.024) On the perception of benefits obtained every increase of 1 unit it will increase 0.135 units of Securing household waste behavior (p value = 0.001). Every increase of 1 unit of perception of eating problems will decrease 0.067 units of Securing Household Waste Behavior (p value = 0.049). Cue unit to act increases 0.078 units of CTPS behavior (p value = 0.023) Every increase of 1 unit of ability / efficacy increases 0.518 units of Securing household waste behavior (p value = 0.001). Each increase of 1 unit of Securing Household Waste Behavior will decrease stunting of 0.071 units (p-value = 0.039) From this study conclusions can be drawn from the perception of vulnerability, perception of seriousness, perceived usefulness, gestures to act, ability / self-efficacy has influence uh positive about household waste management behavior, but the perception of obstacles has a negative influence on Securing household waste. The most influential component of gesture for action is family support.